Choice confidence in the webrooming purchase process: The impact of online positive reviews and the motivation to touch. Issue 5 (1st June 2016) - Flavián, Carlos; Gurrea, Raquel; Orús, Carlos
Abstract: The webrooming purchase process (i.e. searching for information online and then buying the product offline) is the most extended cross‐channel shopping behaviour. With the aim of offering a better understanding of this behaviour, this research relies on information processing and uncertainty reduction theories to propose that consumers use the online information to make the offline purchase with a higher degree of confidence. We examine the effects of a previous online interaction with a product on the preferences and decision at the physical store, as well as on the outcomes of the experience. In this path to purchase, we analyse how positive online customer reviews, as a specific form of electronic word of mouth, help the consumer to improve their experience, given their great potential to reduce the consumer's uncertainty in a purchase situation. In addition, the role of the motivation to touch the product is examined. The results of two studies show that the combination of an online search and an offline purchase improves the consumers' purchase experience in pre‐choice variables (i.e. purchase intentions), choice and post‐choice variables (i.e. search‐process satisfaction and choice confidence). Moreover, reading a positive online customer review influences choice confidence, and all the variables considered in the research when it is received at the physical store. Finally, the results stress the importance of the motivation to touch when studying multichannel shopping behaviour, given its direct and moderating effects on the webrooming purchase process. Implications for theory and practice are discussed. Copyright © 2016 John Wiley & Sons, Ltd.